CONTRASTE DE MÉDIAS NA DETECÇÃO DOS EFEITOS DE ESPAÇAMENTO ENTRE LINHAS E FORMAS DE ADUBAÇÃO EM CANOLA - Silva, Adair J. d.; Schiavo, Jordana; Battisti, Gabriel K.; Bandeira, Taiane P.; Boff, José T.; Wentz, Renan; Uhde, Leonir T.; Maixner, Adriano R.; Krüger, Cleusa A. M. B.; Silva, José A. G. d. (Salão do Conhecimento, 2013)
Resumo